The Reproduction and Activity Coordination Methods of Chrysopa Carnea Sterh. in a Biological Laboratory against Pests in Agriculture - Xudaynazarovich, Buronov Yusuf; Husanovna, Saidova Zuxra; Miraxmatovich, Tog‘ayev Suxrobjon; Musurmonovna, Abdumuminova Muqaddam; Xujamurotovich, Sharipov Shavkat; Azimovich, To‘raev Nurmuxammad; Nurmamatovich, Turdiev Xolmurod; Aripovna, Utanbaev Muxabbat (American Journal of Biodiversity, 2025)
This article explores the cultivation standards of Chrysopa carnea (common green lacewing) as a biological control agent under laboratory and field conditions in Uzbekistan. The main quality indicators of the bioproduct, including the body and wing lengths of mature individuals, egg-laying activity, survival rate, damage indicators, and sex ratio, were determined. The study confirmed that optimal parameters for using C. carnea as a high-quality biological agent in agro-ecosystems were identified, making it possible to develop an effective biological control system based on these findings. The results are of significant importance in organising environmentally safe and sustainable pest control.